The growth act framework: an acceptance and commitment therapy-based group counseling intervention for promoting student flourishing - Nur Tsana Rahima; Gian Sugiana Sugara; Cucu Arumsari (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
This study addressed the need to promote students’ positive psychological well-being amid increasing academic, emotional, and social challenges during adolescence. The study examined the effectiveness of an Acceptance and Commitment Therapy (ACT)-based group counseling intervention in enhancing flourishing among senior high school students. ACT was selected because it aims to enhance psychological flexibility, a key mechanism that enables individuals to pursue meaningful and value-consistent lives despite experiencing psychological distress, thereby supporting the development of flourishing. A quasi-experimental one-group pretest–posttest design was employed. An initial screening was conducted with 149 students, from whom 16 students with low to moderate flourishing levels who met the inclusion criteria were purposively selected for the intervention. Flourishing was assessed using the Integrative Multidimensional Flourishing Scale (IMFS; Cronbach’s α = .93), alongside measures of psychological flexibility, depression, anxiety, and stress. Data were analyzed using the Shapiro–Wilk test, paired-samples t-test, Cohen’s d effect size, and the Reliable Change Index (RCI). The findings demonstrated significant improvements in students’ flourishing and psychological flexibility, accompanied by reductions in psychological distress. The intervention produced a very large effect on flourishing (Cohen’s d = 2.68), with reliable positive changes observed across participants. These findings support ACT-based group counseling as an effective school-based promotive intervention for strengthening students’ psychological well-being and adaptive functioning.